(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
There is no doubt that the murder of Jamal Khashoggi has brought about dramatic changes in the politics of the Middle East, and the key players; U.S., Saudi Arabia and Turkey are all playing different roles in shaping opinion in the region in the aftermath of the murder. While Turkey continues to push for justice for the murder of the journalist, the U.S. is seen to be divided between support for Saudi Arabia and call for justice, and Saudi Arabia on its part is pushing hard to see that it overcomes all attempts to undermine its government and leadership. This article argues that the murder of the journalist has pushed Saudi Arabia into taking steps that would ensure its survival and dominance in the region. The Saudi regime appears to be stepping up its power in the region and has reached out to neighbors and renewed its ties with its Gulf partners and wider Middle East, including Syria to neutralize all attempts by Turkey to undermine its regime.